Hierarchical porous titanium silicalite molecular sieve TS-1 and synthesis method thereof

CN119841328AActive Publication Date: 2025-04-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311348426.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-18
Estimated Expiration
2043-10-17

Smart Images

  • Figure CN119841328A_ABST
    Figure CN119841328A_ABST
Patent Text Reader

Abstract

The invention discloses a hierarchical porous titanium silicalite molecular sieve TS-1 and a synthesis method thereof. The method comprises the following steps: S1, mixing raw materials containing a silicon source, a titanium source, a quaternary ammonium base template agent and water to obtain an initial gel mixture A, and heating and crystallizing I under a closed condition to obtain a crystal blank solution I; s2, mixing raw materials containing a silicon source, an alkali source R, water, a titanium source and a protective agent S to obtain a gel mixture II; and S3, mixing the crystal blank solution I in the step S1 and the gel mixture II in the step S2 to obtain a gel mixture III, and heating and crystallizing the gel mixture III under a closed condition to obtain the hierarchical porous titanium silicalite molecular sieve TS-1. According to the synthesis method provided by the invention, the TS-1 single crystal molecular sieve with the meso-microporous hierarchical structure can be directly synthesized under the assistance of the high-activity crystal embryo solution containing the crystal embryo particles with the super-large specific surface area under the condition that only a small amount of microporous template agent is used.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of molecular sieves, and in particular relates to a multi-level porous titanium silicon molecular sieve TS-1 and a synthesis method thereof. Background Art

[0002] Since its first synthesis in 1983, titanium silicalite (TS-1) has been widely used in the preparation of fine chemicals due to its excellent catalytic performance in clean reaction systems with hydrogen peroxide as an oxidant (such as olefin epoxidation, phenol hydroxylation, etc.). However, the synthesis cost of TS-1 zeolite has always been high due to the limitation of synthetic raw materials, which limits its large-scale application. On the other hand, the smaller pore size in traditional TS-1 zeolite also limits its catalytic conversion of large molecular reactants.

[0003] The main reason for the high cost of TS-1 zeolite synthesis is that a large amount of expensive organic template agent tetrapropylammonium hydroxide (TPAOH), organic silicon source tetraethyl orthosilicate (TEOS) and organic titanium source tetrabutyl titanate (TBOT) are required in the synthesis process.

[0004] On the other hand, the prior art discloses a method of synthesizing multi-level pore TS-1 molecular sieves by introducing mesoporous or macroporous pore formers into the TS-1 zeolite synthesis system, but these mesoporous pore formers are usually complex in structure and costly, and some of them require a complicated synthesis process to obtain, and these mesoporous pore formers usually need to be calcined and removed when the molecular sieve is used, which also pollutes the environment. In addition to introducing pore formers, nano TS-1 molecular sieves are synthesized by increasing the number of seed crystals, but solid-liquid separation of ultrafine nano molecular sieves is usually difficult. Summary of the invention

[0005] In view of this, the present invention provides a multi-level pore titanium silicate molecular sieve TS-1 and a synthesis method thereof, the main purpose of which is to solve the technical problems of high cost, complex operation and environmental unfriendliness in the synthesis method of the multi-level pore structure of titanium silicate molecular sieve TS-1.

[0006] In one aspect, the present invention provides a method for synthesizing a multi-level porous titanium silicon molecular sieve TS-1, the method comprising the following steps:

[0007] S1: mixing raw materials containing a silicon source, a titanium source, a quaternary ammonium base template and water to obtain an initial gel mixture A, and heating and crystallizing the initial gel mixture A under a closed condition to obtain a crystal blank solution I;

[0008] S2: Mixing raw materials containing silicon source, alkali source R and water, titanium source and protective agent S to obtain gel mixture II;

[0009] S3: The crystal blank solution I in step S1 and the gel mixture II in step S2 are mixed to obtain a gel mixture III. The gel mixture III is heated and crystallized under closed conditions to obtain the multi-level porous titanium silicon molecular sieve TS-1.

[0010] The present invention provides a method for synthesizing a multi-level porous titanium silicon molecular sieve TS-1 molecular sieve. Only a small amount of microporous template agent is used in the process of synthesizing a titanium silicon-based embryo solution, and no hard template agent is used. The amount of microporous template agent used is only 1 / 10 to 1 / 20 of that in other conventional methods, thereby solving the problems of high molecular sieve cost and environmental pollution caused by the high price and high toxicity of small molecule microporous organic template agents and mesoporous pore-forming agents. At the same time, the product has a high framework Ti content and does not contain non-framework Ti and TiO2 species.

[0011] Optionally, in step S1, the molar ratio of the silicon source, the titanium source, the quaternary ammonium base template and the water in the initial gel mixture A is:

[0012] Template: SiO2 = 0.10-0.50:1;

[0013] TiO2:SiO2=0.02~0.05:1;

[0014] H2O:SiO2=4~20:1;

[0015] The molar number of the silicon source is calculated as the molar number of SiO2, the molar number of the titanium source is calculated as the molar number of TiO2, the molar number of the template is calculated as the molar number of the quaternary ammonium base, and the water is calculated as the molar number of H2O.

[0016] Optionally, the molar ratio of template:SiO2 in the initial gel mixture A is selected from any value among 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50 or any range between two values.

[0017] Optionally, in the initial gel mixture A,

[0018] The molar ratio of template: SiO2 is preferably 0.15 to 0.45;

[0019] The molar ratio of template: SiO2 is preferably 0.20 to 0.40;

[0020] The molar ratio of TiO2:SiO2 is preferably 0.03-0.05:1;

[0021] The molar ratio of H2O:SiO2 is preferably 6-18.

[0022] Optionally, the molar ratio of TiO2:SiO2 in the initial gel mixture A is selected from any value among 0.02, 0.03, 0.04, 0.05 or any range between the two.

[0023] Optionally, the molar ratio of H2O:SiO2 in the initial gel mixture A is selected from any value among 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or any range between two values.

[0024] Optionally, in step S2, the molar ratio of the silicon source, the titanium source, the alkali source R, the protective agent S and the water in the gel mixture II is:

[0025] SiO2: TiO2: R: S: H2O=1: (0.02~0.10): (0.02~0.20): (0.02~

[0026] 0.2): (6-30);

[0027] Among them, the molar number of the silicon source is calculated as the molar number of SiO2, the molar number of the titanium source is calculated as the molar number of TiO2, the molar number of R is calculated as the molar number of the alkali source R, the S is calculated as the molar number of the protective agent S, and the water is calculated as the molar number of H2O.

[0028] Optionally, in step S2, the molar ratio of the silicon source, the titanium source, the alkali source R, the protective agent S and the water in the gel mixture II is:

[0029] SiO2: TiO2: R: S: H2O=1: (0.02~0.10): (0.02~0.20): (0.02~

[0030] 0.20):(10~40).

[0031] Optionally, in step S2, in the gel mixture II,

[0032] R: SiO2 = 0.02-0.15;

[0033] H2O:SiO2=12-20;

[0034] TiO2:SiO2=0.02-0.05;

[0035] S:SiO2=0.02~0.12.

[0036] Optionally, the gel mixture II in step S2 is obtained by mixing the initial gel mixture B and the initial gel mixture C;

[0037] The initial gel mixture B is obtained by mixing a silicon source, an alkali source R and water; the molar ratio of each component in the initial gel mixture B is:

[0038] R: SiO2 = 0-0.20:1;

[0039] H2O:SiO2=6-30:1;

[0040] The initial gel mixture C is obtained by mixing a titanium source and a protective agent S; the molar ratio of each component in the initial gel mixture C is:

[0041] S: TiO2 = 1 to 5:

[0042] Among them, the molar number of the silicon source is calculated as the molar number of SiO2, the molar number of the titanium source is calculated as the molar number of TiO2, the molar number of the alkali source R is calculated as the molar number of R, the protective agent S is calculated as the molar number of S, and the water is calculated as the molar number of H2O.

[0043] Optionally, in the initial gel mixture B, the molar ratio of R:SiO2 is selected from any value among 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.12, 0.14, 0.16, 0.18, 0.20 or any range between two values;

[0044] In the initial gel mixture B, the molar ratio of H2O:SiO2 is selected from any value among 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 or any range between two thereof.

[0045] Optionally, in the initial gel mixture C, the molar ratio of S:TiO2 is selected from any value of 1, 2, 3, 4, 5 or any range between two values.

[0046] Optionally, the structural formula of the quaternary ammonium base template is Formula I:

[0047]

[0048] Among them, R in Formula I 1 , R 2 , R 3 , R 4 Each independently selected from any one of C1 to C4 alkyl groups, R 1 , R 2 , R 3 and R 4 Same or different.

[0049] Optionally, the quaternary ammonium base template is selected from tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide; preferably tetrapropylammonium hydroxide.

[0050] Optionally, in step S2, the initial gel mixture C is added dropwise to the initial gel mixture B under stirring to obtain the gel mixture II.

[0051] Optionally, in step S3, the product after heating and crystallization II is separated, washed and dried to obtain nano-sheet-shaped hierarchical pore TS-1 molecular sieve.

[0052] Optionally, in step S3, the molar content of SiO2 in the crystal blank solution I is 3-10% of the molar content of SiO2 in the gel mixture II.

[0053] Optionally, in step S3, the molar content of SiO2 in the crystal blank solution I is the molar content of SiO2 in the gel mixture II, selected from any value of 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range between any two of them.

[0054] Optionally, in step S1, crystallization I is dynamic crystallization.

[0055] Optionally, in step S1, the temperature of the crystallization I is 60-140° C., and the time of the crystallization I is 0.5-24 h; preferably 80-120° C., 2-16 h.

[0056] Optionally, in step S1, the temperature of the crystallization I is selected from any value of 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, or a range between any two of them; the time of the crystallization I is selected from any value of 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24h, or a range between any two of them.

[0057] Optionally, in step S3, the temperature of the crystallization II is 140-220° C., and the time of the crystallization II is 0.5-48 h, preferably 160-200, 1-12 h.

[0058] Optionally, in step S3, the temperature of the crystallization II is selected from any value of 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, or any range between two thereof; the time of the crystallization I is selected from any value of 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 28, 30, 32, 35, 38, 40, 42, 44, 46, 48h, or any range between two thereof.

[0059] Optionally, the silicon source in the initial gel mixture A is selected from at least one of silica sol, methyl orthosilicate and ethyl orthosilicate; and the titanium source is selected from at least one of tetraethyl titanate, tetrabutyl titanate and titanium isopropoxide.

[0060] Optionally, the silicon source in the gel mixture II is selected from at least one of silica sol, silica gel, chromatography column silica gel, methyl orthosilicate, ethyl orthosilicate and white carbon black.

[0061] Optionally, the titanium source is selected from at least one of tetraethyl titanate, tetrabutyl titanate, titanium tetrachloride, titanium sulfate and titanium isopropoxide.

[0062] Optionally, the alkaline source R in the gel mixture II is selected from a compound having a structure of formula I:

[0063]

[0064] Wherein, in formula I, R1, R2, and R3 are each independently selected from H or an alkyl group having 1 to 4 carbon atoms.

[0065] Optionally, the alkali source R is selected from at least one of ammonia water, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, n-propylamine, di-n-propylamine, tri-n-propylamine, isopropylamine, diisopropylamine, triisopropylamine, n-butylamine, di-n-butylamine and tri-n-butylamine.

[0066] Optionally, the protective agent S is selected from at least one of ethanol, isopropanol and acetylacetone.

[0067] Optionally, in step S1, the solid in the crystal blank solution I has an amorphous structure, a particle size of 10 to 20 nm, and a five-membered ring structure is contained in the particle structure.

[0068] Optionally, in step S3, the titanium silicon molecular sieve TS-1 is calcined in air at a temperature of 400 to 600°C.

[0069] Optionally, in step S3, the calcination temperature is selected from any value of 400°C, 420°C, 450°C, 470°C, 190°C, 500°C, 520°C, 550°C, 580°C, 600°C or any range between two of them.

[0070] In a second aspect, the present invention provides a titanium silicalite molecular sieve TS-1, which is synthesized by the above-mentioned synthesis method.

[0071] Optionally, the titanium silicalite molecular sieve TS-1 has an MFI topological structure, wherein the Ti species has a four-coordinate structure.

[0072] Optionally, the titanium silicon molecular sieve TS-1 has a multi-level pore structure of medium and large pores and micropores; the pore volume of the medium and large pores is 0.2 to 0.3 cm 3 g -1 The pore sizes of the mesopores are distributed between 20 and 120 nm.

[0073] Optionally, the titanium silicalite molecular sieve TS-1 has a flake-like morphology, and the length, width and thickness of the flakes are 600-800 nm, 400-600 nm and 80-120 nm, respectively.

[0074] In the present application, the "silicon-titanium ratio" refers to the molar ratio of silicon to titanium.

[0075] Compared with the prior art, the present invention has the following beneficial effects:

[0076] (1) The method provided by the present invention can synthesize hierarchical pore titanium silicon single crystal molecular sieves with mesoporous structure by using only a small amount of microporous template agent with the assistance of high-activity embryo solution without introducing a hard template agent, and the product yield reaches 90%.

[0077] (2) The product obtained by the method provided by the present invention has a single Ti coordination, a high framework Ti content, and a high product yield.

[0078] (3) Compared with the prior art, the method provided by the present invention does not use a hard template in the entire process, nor does it require cumbersome post-treatment and separation processes. The synthesis cost is lower, the crystallization time is greatly shortened, the production efficiency is improved, and the production energy consumption is reduced; it is conducive to the large-scale production of titanium silicon molecular sieves. BRIEF DESCRIPTION OF THE DRAWINGS

[0079] Figure 1 The X-ray diffraction pattern of the embryo powder 1# provided in Example 1 of the present invention;

[0080] Figure 2 The infrared spectrum of the embryo powder 1# provided in Example 1 of the present invention;

[0081] Figure 3The X-ray diffraction pattern of sample 1# provided in Example 1 of the present invention;

[0082] Figure 4 This is a transmission electron microscope image of sample 1# provided in Example 1 of the present invention;

[0083] Figure 5 The ultraviolet diffuse reflectance spectrum of sample 1# provided in Example 1 of the present invention;

[0084] Figure 6 The physical adsorption spectrum of sample 1# provided in Example 1 of the present invention;

[0085] Figure 7 A pore size distribution diagram of sample 1# provided in Example 1 of the present invention;

[0086] Figure 8 The X-ray diffraction pattern of the embryo powder comparison sample 1# provided in Comparative Example 1 of the present invention;

[0087] Fig. 9 This is the ultraviolet diffuse reflectance spectrum of comparative sample 1# provided in comparative example 1 of the present invention. DETAILED DESCRIPTION

[0088] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.

[0089] Unless otherwise specified, the raw materials and reagents used in this application were purchased from commercial sources and used directly without treatment. The instruments and equipment used adopted the schemes and parameters recommended by the manufacturers.

[0090] The analysis method in the examples of this application is as follows:

[0091] X-ray powder diffraction phase analysis (XRD) was performed using an X'Pert PRO X-ray diffractometer from PANalytical of the Netherlands, with a Cu target, a Kα radiation source (λ=0.15418 nm), a voltage of 40 KV, and a current of 40 mA.

[0092] The elemental composition was determined using a Philips Magix 2424 X-ray fluorescence analyzer (XRF).

[0093] Low-temperature nitrogen physical adsorption was used to characterize the pore structure of the sample. The instrument used was the ASAP2020 physical adsorption instrument produced by Micromeritics. The BET formula was used to calculate the specific surface area, and the BJH formula was used to calculate the pore distribution.

[0094] The yield of the sample was calculated according to the following formula:

[0095] Yield = (mass of the sample after calcination) ÷ (mass of SiO2 in mixture III + mass of TiO2) × 100%.

[0096] Example 1 Sample 1 # Synthesis

[0097] Using tetraethyl orthosilicate as silicon source, tetraethyl titanate as titanium source, and tetrapropylammonium hydroxide as template, a mixed solution with a homogeneous molar ratio of 1SiO2:0.025TiO2:0.35TPAOH:16H2O was prepared, and then placed in a synthesis reactor with a polytetrafluoroethylene liner and crystallized at 120°C for 18 hours to obtain a homogeneous embryo solution I. A portion of the embryo solution was neutralized with acetic acid in a stoichiometric ratio to obtain a solid powder, and the powder was dried and calcined to obtain a sample, which was recorded as embryo powder 1#.

[0098] Using methyl orthosilicate as silicon source, tetrabutyl titanate as titanium source, diethylamine as alkali source and anhydrous ethanol as protective agent, SiO2:0.028TiO2:0.08C4H 11 N: 0.05S: 12H2O mixed solution II, at this time, embryo solution I is added to the mixed solution II, wherein the SiO2 content in the embryo solution I accounts for 10% of the SiO2 content in the mixed solution II, to form a final mixed solution, the mixed solution is placed in a synthesis kettle with a polytetrafluoroethylene liner and crystallized at 175°C for 8 hours to obtain a titanium silicon molecular sieve, the product is centrifuged, washed, dried, and calcined to obtain the final molecular sieve product, recorded as sample 1#, and the XRF results show that the product's Si / Ti=38.6.

[0099] Example 2 Preparation of samples 2# to 19#

[0100] Sample 2 # ~19 # The raw material types, raw material ratios, and crystallization conditions are shown in Table 1. The batching process is the same as that of Sample 1 in Example 1. # Preparation.

[0101] Table 1. Ingredients and crystallization conditions for molecular sieve synthesis in Examples 1 to 19

[0102]

[0103]

[0104] Comparative Example 1 Comparative Sample 1 # Preparation

[0105] The specific proportion of ingredients, the preparation process and the crystallization conditions are the same as those of Sample 1 in Example 1. # The preparation method is as follows, except that no Ti source is added during the preparation of the embryo solution I, and the embryo solution is neutralized with acetic acid in a stoichiometric ratio to obtain a solid powder, and the obtained sample is recorded as embryo powder comparative sample 1#. The final sample synthesized using the embryo solution synthesized in comparative example 1 is recorded as comparative sample 1#.

[0106] Example 20 Sample 1 # ~19 # XRD and IR analysis of synthetic embryo solution including solid

[0107] The crystal embryo powders corresponding to the crystal embryo solutions prepared in the embodiment are all amorphous in XRD. However, the infrared IR characterization contains a large number of characteristic peaks attributable to the 5-membered ring structure that are consistent with the positions of MFI zeolite, such as the typical representative. Figure 1 From the XRD spectrum of embryo powder 1#, it can be seen that the embryo powder is amorphous. The XRD spectrum results of embryo powders 2#-19# are similar to Figure 1 Close, indicating that they are all amorphous structures; Figure 2 This is the IR spectrum of embryo powder 1#. It can be seen that at 550cm -1 There are characteristic peaks attributable to the 5-membered ring structure nearby. The IR spectra of embryo powder 2#-19# are similar to Figure 2 Close, at 550cm -1 Vibration peaks consistent with MFI structure zeolite can be observed nearby, indicating that the synthesized embryo contains zeolite structural units.

[0108] Embodiment 21

[0109] Sample 1 # ~19 # XRD, SEM, UV-Vis, N2 physical adsorption and pore size distribution analysis of sample 1 were carried out by X-ray diffraction, scanning electron microscopy and UV diffuse reflectance. # ~19 # Conduct analysis.

[0110] Sample 1 prepared in Example # ~19 # All of them are TS-1 molecular sieves with high purity and high crystallinity and MFI topology, such as Figure 3 Medium sample 1 # XRD spectrum of sample 2 # ~19 # The XRD results show that the position and shape of the diffraction peaks are basically the same, and the relative peak intensity fluctuates within the range of ±5% depending on the synthesis conditions.# ~19 # It has the characteristics of MFI structure and has no impurity crystals.

[0111] Sample 1 # ~19 # All of them have nano-flake morphology, typical examples are Figure 4 From the SEM image of sample 1#, we can see that the product has a flake structure with a size of about 600nm*400nm*100nm. The particle size is relatively uniform. The cross section shows that it is composed of a large number of small particles with a size of 10-20nm. # ~19 # The SEM images show that the product morphology and particle size are Figure 1 Sample 1# is close in size.

[0112] Sample 1 # ~19 # All Ti species exist as tetracoordinated framework Ti species, typical representatives of which are Figure 5 From the UV-Vis graph of sample 1#, it can be seen that the Ti in the product is mainly in the form of tetracoordinate (210-220nm), and there is almost no non-framework Ti (230-270nm) and nano-TiO2 (310-330nm); sample 2 # ~19 # The UV-Vis graph of is similar to that of sample 1#, mainly existing in the form of tetracoordinate species, without any non-framework Ti and TiO2 species.

[0113] Figure 6 and Figure 7 The physical adsorption curve and pore size distribution diagram of the product are shown respectively. It can be seen that under the premise of ensuring the micropore volume of the product, the medium and macropore volume of the product reaches 0.22cm 3 g -1 The pore size distribution of medium and large pores is between 20-120nm; Sample 2 # ~19 # The physical adsorption curve and pore size distribution of Figure 6 and Figure 7 Similarly, it can be seen that the product obtained by the present invention has both high skeleton Ti content and hierarchical pore structure, and the product yield can reach 90%.

[0114] XRD analysis of embryo powder in comparative example 1# compared with sample 1# in Example 22

[0115] Figure 8 This is the XRD spectrum of the embryo powder comparison sample 1#. It can be seen that the seed comparison sample 1# already has a topological structure that can be partially attributed to MFI.

[0116] UV-Vis analysis of Example 23 Comparative Example 1#

[0117] The XRD, SEM and physical adsorption results (not shown) of sample 1# are similar to those of sample 1#; however, its UV-Vis Fig. 9 As shown in the figure, in addition to the framework Ti, the comparative sample 1# also contains a large amount of non-framework Ti species (230-270cm -1 ).

[0118] In Comparative Example 1, no Ti was added to the crystal blank. The crystal blank was crystallized at the same crystallization temperature of 120°C for 18 h. The synthesized crystal blank grew significantly, and the molecular sieve finally synthesized contained a large amount of non-framework Ti species.

[0119] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for synthesizing a multi-level porous titanium silicon molecular sieve TS-1, characterized in that: The method comprises the following steps: S1: mixing raw materials containing a silicon source, a titanium source, a quaternary ammonium base template and water to obtain an initial gel mixture A, and heating and crystallizing the initial gel mixture A under a closed condition to obtain a crystal blank solution I; S2: Mixing raw materials containing silicon source, alkali source R and water, titanium source and protective agent S to obtain gel mixture II; S3: The crystal blank solution I in step S1 and the gel mixture II in step S2 are mixed to obtain a gel mixture III. The gel mixture III is heated and crystallized under closed conditions to obtain the multi-level porous titanium silicon molecular sieve TS-1.

2. The method for synthesizing a multi-level porous titanium silicon molecular sieve TS-1 according to claim 1, characterized in that: In step S1, the molar ratio of the silicon source, the titanium source, the quaternary ammonium base template and the water in the initial gel mixture A is: Template: SiO2 = 0.10-0.50:1; TiO2:SiO2=0.02~0.05:1; H2O:SiO2=4~20:1; The molar number of the silicon source is calculated as the molar number of SiO2, the molar number of the titanium source is calculated as the molar number of TiO2, the molar number of the template is calculated as the molar number of the quaternary ammonium base, and the water is calculated as the molar number of H2O.

3. The method for synthesizing a multi-level porous titanium silicon molecular sieve TS-1 according to claim 1, characterized in that: In step S2, the molar ratio of the silicon source, the titanium source, the alkali source R, the protective agent S and the water in the gel mixture II is: SiO2: TiO2: R: S: H2O=1: (0.02~0.10): (0.02~0.20): (0.02~ 0.2):(6~30); Among them, the molar number of the silicon source is calculated as the molar number of SiO2, the molar number of the titanium source is calculated as the molar number of TiO2, the molar number of R is calculated as the molar number of the alkali source R, the S is calculated as the molar number of the protective agent S, and the water is calculated as the molar number of H2O.

4. The method for synthesizing a multi-level porous titanium silicon molecular sieve TS-1 according to claim 1, characterized in that: The gel mixture II in step S2 is obtained by mixing the initial gel mixture B and the initial gel mixture C; The initial gel mixture B is obtained by mixing a silicon source, an alkali source R and water; the molar ratio of each component in the initial gel mixture B is: R: SiO2 = 0-0.20:1; H2O:SiO2=6-30:1; The initial gel mixture C is obtained by mixing a titanium source and a protective agent S; the molar ratio of each component in the initial gel mixture C is: S: TiO2 = 1-5:1; Among them, the molar number of the silicon source is calculated as the molar number of SiO2, the molar number of the titanium source is calculated as the molar number of TiO2, the molar number of the alkali source R is calculated as the molar number of R, the protective agent S is calculated as the molar number of S, and the water is calculated as the molar number of H2O.

5. The method for synthesizing a multi-level porous titanium silicon molecular sieve TS-1 according to claim 1, characterized in that: The structural formula of the quaternary ammonium base template is Formula I: Among them, R in Formula I 1 , R 2 , R 3 , R 4 Each independently selected from any one of C1 to C4 alkyl groups, R 1 , R 2 , R 3 and R 4 Same or different; Preferably, the quaternary ammonium base template is selected from tetraethylammonium hydroxide, tetrapropylammonium hydroxide, and tetrabutylammonium hydroxide; Preferably, in step S3, the molar content of SiO2 in the crystal blank solution I is 3-10% of the molar content of SiO2 in the gel mixture II.

6. The method for synthesizing a multi-level porous titanium silicon molecular sieve TS-1 according to claim 1, characterized in that: In step S1, the temperature of the crystallization I is 60 to 140° C., and the time of the crystallization I is 0.5 to 24 hours; Preferably, in step S3, the temperature of the crystallization II is 140-220° C., and the time of the crystallization II is 0.5-48 h; Preferably, the silicon source in the initial gel mixture A is selected from at least one of silica sol, methyl orthosilicate and ethyl orthosilicate; the titanium source is selected from at least one of tetraethyl titanate, tetrabutyl titanate and titanium isopropoxide; Preferably, the silicon source in the gel mixture II is selected from at least one of silica sol, silica gel, chromatography column silica gel, methyl orthosilicate, ethyl orthosilicate and white carbon black; the titanium source is selected from at least one of tetraethyl titanate, tetrabutyl titanate, titanium tetrachloride, titanium sulfate and titanium isopropoxide.

7. The method for synthesizing a multi-level porous titanium silicon molecular sieve TS-1 according to claim 1, characterized in that: The alkaline source R in the gel mixture II is selected from a compound having a structure of formula II: Wherein, in formula II, R1, R2, and R3 are each independently selected from H or an alkyl group having 1 to 4 carbon atoms; Preferably, the alkaline source R in the gel mixture II is selected from at least one of aqueous ammonia, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, n-propylamine, di-n-propylamine, tri-n-propylamine, isopropylamine, diisopropylamine, triisopropylamine, n-butylamine, di-n-butylamine and tri-n-butylamine; The protective agent S is selected from at least one of ethanol, isopropanol and acetylacetone.

8. The method for synthesizing a hierarchical pore titanium silicon molecular sieve TS-1 according to claim 1, characterized in that: In step S1, the solid in the crystal blank solution I has an amorphous structure, a particle size of 10 to 20 nm, and a five-membered ring structure in the particle structure; Preferably, in step S3, the titanium silicon molecular sieve TS-1 is calcined in air at a temperature of 400 to 600°C.

9. A multi-level pore titanium silicon molecular sieve TS-1, characterized in that: The titanium silicon molecular sieve is synthesized by the synthesis method of titanium silicon molecular sieve TS-1 described in any one of claims 1 to 8.

10. The multi-level pore titanium silicon molecular sieve TS-1 according to claim 9, characterized in that: The titanium silicon molecular sieve TS-1 has a multi-level pore structure of medium and large pores and micropores; the pore volume of the medium and large pores is 0.2 to 0.3 cm 3 g -1 , the pore size distribution of the mesopores and macropores is between 20 and 120 nm; Preferably, the titanium silicon molecular sieve TS-1 has an MFI topological structure, in which the Ti species has a tetracoordinate structure; the titanium silicon molecular sieve TS-1 has a flake morphology, and the length, width and thickness of the flakes are 600-800nm, 400-600nm and 80-120nm, respectively.

Citation Information

Patent Citations

  • Method for quickly synthesizing small-crystallite titanium-silicon molecular sieve in cheap system

    CN101913620A

  • Method for synthesizing titanium-silicalite molecular sieve

    CN103896301A

  • Method for preparing nano titanium silicalite molecular sieve at low cost

    CN112758951A

  • Method of synthesizing titanium silicon molecular sieve using complexig agent to raise titanium source stability

    CN1751996A